Avaliação da atividade anti-inflamatória da atorvastatina e de sua ação no diâmetro alveolar em modelo de enfisema elastase-induzido em ratos - Boiati, Raphael Fernando (2010)
Background: Recent studies have demonstrated some statin pleiotropic effects, such as anti-inflammatory activity. Atorvastatin, in addition to cholesterol lowering action, has shown anti-inflammatory activities that could reduce the destructive effects linked to emphysema which could reduce the destructive effects of chronic inflammation associated with pulmonary emphysema. This study evaluated the protective effect of atorvastatin on the destruction of alveolar structure and the inflammatory process involved in elastase-induced emphysema in rats. Methods: 32 male rats divided into four groups N = 8: control (C), emphysema (E), atorvastatin (A) and emphysema atorvastatin (EA). Groups C and A received intratracheal instillation of 0,2 ml of saline and groups E and EA received 0,2 ml of porcine pancreatic elastase to induce emphysema. Groups A and EA atorvastatin (20mg/kg) and groups C and E received vehicle (CMC) once daily by gavage for 25 days. After this period, there is the euthanasia of animals and the lungs removed for analysis. Histological lung sections were stained with hematoxylin eosin and examined the alveolar diameter (LM) by linear intercept as a measure of interalveolar septal wall. Results: The data show the development of pulmonary emphysema after intratracheal administration of elastase, but treatment with atorvastatin showed no significant changes in LM, nitric oxide or the number of leukocytes, compared with the elastase group, reduction was not observed or inhibition of pulmonary emphysema induced by intratracheal elastase. Conclusions: Our results suggest that the elastase infusion model is effective for developing emphysema in rats, but the administration of atorvastatin did not alter the course of the disease, as observed in studies with other statins.